Islamic Method of Education by Qudwah Hasanah in Surah Ahzab Verse 21 (Analytical Studies in Tafsir Munir Dr. Wahbah Az-Zuhaili) - Heru Saiful Anwar; Rizka Tiodara (Educan : Jurnal Pendidikan Islam, 2021)
The loss of the essence of an educator's qudwah al-hasanah is one of the causes of personal damage and behavior of a child, even though the Prophet has taught his followers related to the best of role model. Islamic education has an important role in advancing civilization. One of the methods applied in Islamic education is by qudwah al-hasanah because is a basic method of educating and a child learns by sees and imitates. Seeing this, the method of accuracy is considered very important to be reviewed in the al-Qur’an surah al-Ahzab verse 21 which discusses the method of Islamic education with accuracy as taught by the Prophet. The purpose of this research is 1) To find out the tafsir of al-Ahzab verse 21 according to the commentary of Al Munir Dr. Wahbah Az-Az-Zuhaili. 2) To know the method of Islamic education with qudwah al-hasanah contained in surah al-Ahzab verse 21. This type of discussion is literature research or library research where researchers get data from reading books that are relevant to the titles and written documentation obtained from library books. Particularly with regard to the tafsir of the text of the Al-Qur'an Surah al-Ahzab verse 21 through an analytical approach with a descriptive-qualitative method. Then processed according to the ability of the author. The writing of this journal discusses the method of Islamic education with qudwah al-hasanah in surah al-Ahzab verse 21 according to Tafsir Al-Munir. Dr. Wahbah Az-Az-Zuhaili 1) The tafsir of surah al-Ahzab verse 21 according to the Tafsir of Al-Munir explains that the Messenger of Allah is the best role model for mankind and should emulate the Prophet in his words, deeds and in various circumstances. Especially in terms of courage, courage to go forward, struggle and patience, and encouragement to always remember Allah and hope in Allah. 2) The method of education using qudwah al-hasanah taught by the Prophet in Surah al-ahzab 21 includes courage, courage to go forward, patience and struggle. This is the description of the discussion of Islamic education methods with qudwah-al hasanahcontained in the Al-Ahzab verse 21 (Study of Tafsir Al-Munir of Dr. Wahbah Az-Az-Zuhaili). It is hoped that educators and teachers to educate children with the qudwah al-hasanah method, so that they can become the best examples in words, deeds, and under any circumstances. The author acknowledges that this discussion still has many shortcomings, so the author hopes all readers and subsequent discussants to complete the deficiencies in this discussion so that it becomes perfect and provides benefits.